2022
DOI: 10.1007/s00705-022-05534-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of replication and variations in genome segments of a bat reovirus, BatMRV/B19-02, by RNA-seq in infected Vero-E6 cells

Abstract: Mammalian orthoreoviruses (MEVs) that can cause enteric, respiratory, and encephalitic infections have been identified in a wide variety of mammalian species. Here, we report a novel MRV type 1 strain detected in Miniopterus schreibersii that may have resulted from reassortment events. Using next-generation RNA sequencing (RNA-seq), we found that the ratios of the RNA levels of the 10 reovirus segments in infected cells were constant during the late stages of infection. We also discovered that the relative abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In the present study, MRVs were not detected in farm A, whereas MRV1 and MRV2 were isolated from farm B, which suggests that multiple serotypes were present in that pig farm. Phylogenetic analysis based on the partial S1 gene showed that our MRV1 isolate was most closely related to the MRV1 isolated from a bat in South Korea [18] (94.31 % identity). This result suggests that our MRV1 isolate may have been derived from the viruses recently circulating in South Korean bats populations.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the present study, MRVs were not detected in farm A, whereas MRV1 and MRV2 were isolated from farm B, which suggests that multiple serotypes were present in that pig farm. Phylogenetic analysis based on the partial S1 gene showed that our MRV1 isolate was most closely related to the MRV1 isolated from a bat in South Korea [18] (94.31 % identity). This result suggests that our MRV1 isolate may have been derived from the viruses recently circulating in South Korean bats populations.…”
Section: Discussionmentioning
confidence: 78%
“…4. Sequence analysis showed that MRV1-GmmTN1 was closely related to MRV1/Bat/Korea/B19-02/2019 [18], a variant isolated from a bat in South Korea, with 94.31 % nucleotide identity; two MRV2 strains (MRV2-GmmTN9, MRV2-GmmTN13) were closely related to those of MRV2/Pig/USA/66848/2005 that was isolated from pigs in the United States (no reference) (92.20 and 92.00 % identity, respectively).…”
Section: Isolation Of Mrvs and Phylogenic Analysis Of Their S1 Genesmentioning
confidence: 99%
“…At least four tree shrew MRVs have been described in recent years ( Li et al, 2020 ; Xu et al, 2013 ). Genetic reassortment and intragenic rearrangement events have also been detected in MRVs in a wide range of hosts, including bats, humans, pigs, and minks ( Duncan, 1999 ; Lo et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since its initial isolation from the stools of children in 1954 [ 1 ], MRV has been reported in children with gastroenteritis [ 3 5 ]. In addition, strains of MRV have been detected continually in a wide range of mammals, including pigs [ 6 ], wild boars [ 7 ], cats [ 8 ], dogs [ 9 ], bats [ 10 17 ], and deer [ 18 ], and have also been found in wastewater [ 19 ], indicating the broad host range of this virus. Bats are particularly noteworthy in this regard, in that they are considered to be natural reservoirs of MRV, and a genetically diverse range of strains have been detected in different bat species [ 10 ].…”
mentioning
confidence: 99%
“…Bats are particularly noteworthy in this regard, in that they are considered to be natural reservoirs of MRV, and a genetically diverse range of strains have been detected in different bat species [ 10 ]. However, although bat MRVs have been reported in multiple regions, including Europe [ 9 , 11 ], the United States [ 13 ], China [ 10 , 14 16 ], and Korea [ 17 ], to date, none of these viruses have been detected in Japanese bats, despite the presence of MRV in several mammals in Japan [ 6 9 ]. In this study, we detected and isolated a novel MRV strain from bats in Japan.…”
mentioning
confidence: 99%